Variasi Variasi Leksikal Bahasa Bali di Kecamatan Pekutatan Kajian Dialektologi - Ayu Putri Rukmana, Ni Ketut; Sutama, Putu; Ariana, I Putu (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2026)
This study aims at describing the lexical variations of the Balinese language in Pekutatan District. The data source of this research is the speech of Balinese language speakers in eight villages in Pekutatan District. The data were collected through observation and interview methods using simak and cakap techniques. The analysis was conducted using the distributional method based on structural linguistics and dialectology theories. The results show that lexical variations are distributed across eight villages: 23 in Medewi, 8 in Pulukan, 10 in Pekutatan, 12 in Asahduren, 17 in Manggissari, 8 in Pangyangan, 25 in Gumbrih, and 25 in Pengeragoan.